Fluidized-Bed combustion of coal - NAUDE_DP (Occupational and Environmental Health RU, 2023)
A general review of the literature pertaining to the combustion of coal in an atmospheric fluidized bed of ,inert particles is presented. In particular, the phenomena of fluidization and combustion have been investigated and the status of research and development in various parts of the world is considered. A 300 mm diameter refractory lined open top atmospheric fluidized bed combustor has been built to study the combustion efficiencies and entrainment rates of the fluidized-bed combustion process in shallow fluidized beds, with static bed heights ranging from about ISO mm to 23J mm. A low pressure drop the of distributed was used for all of the tests so as to test a system compatible with most industrial requirements. As the combustor vessel is refractory lined, cooling is provided by supplying air to the rig well in excess of that required for stoichiometric combustion. As a result, no oxygen deficient regions occur within the fluidized bed, ensuring complete combustion of both the fixed carbon component of the coal to carbon dioxide and the volatile component within the bed section. Experimental results have been obtained from the combustion of a coal with a high fines content of which there is at present a supply which exceeds the demand. The coal has been burned in an inert bed comprising a closely graded silica sand. It has been found possible to correlate the combustion efficiencies in terms of the bed temperature, superficial gas velocity and the static bed height within the following ranges of these parameters: Bed Temperature Gas Velocity Static Bed Height 700 to 10000C 0,9 to 1,5 m/s 150 to 230 mm by using a bed material substantially different from the coal feed, it has been found possible to separate the (i) ABSTRACT A